Marmota caligata - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
252. Hoary Marmot Marmota caligata French: Marmotte des Rocheuses / German: Eisgraues Murmeltier / Spanish: Marmota canosa Taxonomy. Arctomys caligatus Eschscholtz, 1829, “im nordlichsten Theile der West- kuiste Amerika’s, haufig an der Bristolbai [= northern areas of the west coast of America, frequently on Bristol Bay].” Restricted by J. A. Allen in 1877 to near Bristol Bay, Alaska, USA. Three subspecies are recognized. Subspecies and Distribution. M. c¢. caligata Eschscholtz, 1829 — Alaska and W Yukon (Canada). M.c.cascadensisA.H.Howell,1914—SWBritishColumbia(Canada)andWWashington(USA). M. c. okanagana King, 1836 — S Yukon, W Northwest Territories, E British Columbia, W Alberta (Canada) to NE Idaho and W Montana (USA). Descriptive notes. Head-body 450-600 mm, tail 170-250 mm; weight 3.6-9 kg. The Hoary Marmot has light-colored pale cream to white anterior dorsal pelage and yellow to tan posterior dorsum, rump, and tail. Head is cream to buff, with dark brown to black on snout, crown, and chin. Feet are often dark brown to black. Venteris pale cream to white. Subspecies okanagana is pale; cascadensis has dark feet and venter. Habitat. Open rocky talus slopes and alpine tundra naturally fragmented and disjunct. Food and Feeding. The Hoary Marmot is an herbivore that feeds primarily on young grasses, shoots of forbs, bulbs, and other herbaceous material growing in open alpine meadows. Breeding. The Hoary Marmot lives in multi-burrow colonies and appears to mate in burrows or soon after spring emergence. Every two years, females give birth to litters of 4-5 young. Activity patterns. Hoary Marmots are diurnal. They are only active for 4-5 months each summer and hibernate in burrows for the remaining 7-8 months ofthe year. It hibernates as family groups beginning in September—October. Movements, Home range and Social organization. Burrows are relatively complex with multiple entrances and extend up to 3 m underground. Hoary Marmots overwinter in communal groups and are highly social. They typically live in family ...